2000
DOI: 10.1080/02791072.2000.10400225
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-as-Usual in the Methamphetamine Treatment Project

Abstract: The Methamphetamine Treatment Project is a multisite trial that compares the effectiveness of eight models of outpatient treatment for methamphetamine dependence to that of the Matrix model. These eight "treatment-as-usual" models represent diverse approaches developed in a variety of settings to serve markedly different populations. The theoretical foundations of these treatments are described as well as the settings in which they are delivered. To facilitate comparisons, details are presented with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…The model operates as an outpatient program using a 16-week psychosocial platform with group therapy sessions, family education, 12-step meetings, and routine urine testing (Obert, McCann, Brethen, Marinelli-Casey, & Rawson, 2000). The TAU intervention is composed of eight diverse outpatient cognitive-behavioral treatment approaches, ranging from individual or group-based counseling sessions using different intensities (i.e., once per week vs. thrice weekly) and lasting between 8 and 16 weeks (Galloway et al, 2000).…”
Section: Treatment Conditionsmentioning
confidence: 99%
“…The model operates as an outpatient program using a 16-week psychosocial platform with group therapy sessions, family education, 12-step meetings, and routine urine testing (Obert, McCann, Brethen, Marinelli-Casey, & Rawson, 2000). The TAU intervention is composed of eight diverse outpatient cognitive-behavioral treatment approaches, ranging from individual or group-based counseling sessions using different intensities (i.e., once per week vs. thrice weekly) and lasting between 8 and 16 weeks (Galloway et al, 2000).…”
Section: Treatment Conditionsmentioning
confidence: 99%
“…The MTP's procedures and comparison conditions were reported by Huber et al (2000) and Galloway et al (2000). Results showed better treatment attendance as well as retention and fewer methamphetamine-positive urinalysis findings during treatment but no difference between groups at treatment discharge or at the 6-month follow-up (Rawson et al, 2004).…”
Section: The Mtpmentioning
confidence: 77%
“…At this time, the lack of methamphetamine-specific inpatient or outpatient substance-abuse programs for adolescents should not stand as a barrier to treatment. While it is possible that future methamphetamine-specific treatment programs may produce relatively greater improvements for adolescent methamphetamine users, especially as more becomes known about the clinical detriments of methamphetamine abuse and dependence, researchers have not yet demonstrated that methamphetamine-specific treatment approaches produce superior post-treatment improvement in comparison to a range of standard treatment-as-usual protocols [9,10].…”
Section: Discussionmentioning
confidence: 96%